Towards a paradigm shift in pediatric rehabilitation: accelerating the uptake of evidence on participation into routine clinical practice. Issue 9 (24th April 2022) - Anaby, D.; Khetani, M.; Piskur, B.; van der Holst, M.; Bedell, G.; Schakel, F.; de Kloet, A.; Simeonsson, R.; Imms, C.
Abstract: Purpose: Evidence for the importance of focusing on participation to promote health and wellbeing in childhood-onset disability exists, but practice is slow to change. This paper provides a knowledge translation roadmap to accelerate uptake of participation evidence into day-to-day practice. Materials and methods: A structured roadmap to guide knowledge translation initiatives for implementing participation-based practices in co-creation with service users was developed based on elements from: the Five-factorframework for predicting implementation outcomes, the Cultural Cone framework, and the Knowledge-to-Action model. Results: Guiding principles paired with examples of multi-component knowledge implementation strategies to facilitate readiness for change by stakeholders at the micro (e.g., client/family, service providers), meso (e.g., administrators within organisations such as rehabilitation centres, hospitals, schools) and macro (e.g., local and governmental policy, regulatory bodies) levels are introduced. Solution-based strategies are provided to facilitate "readiness to change" for each stakeholder group. The strategies are examples for successful implementation of evidence-based interventions/approaches that can be contextualized across settings. Conclusions: The knowledge translation roadmap can assist children and families, service providers, administrators, and policymakers to bridge existing knowledge-to-practice gaps surrounding participation. Partnering and collaborating through a "family-clinician-manager-community leader-policymaker" synergy is key for achieving strategic practice change focussed on participation. Implications for Rehabilitation: Sound evidence surrounding the topic of participation, including effective assessments and interventions, is available and ready for use. Shifting towards participation-focused practices for children and youth with disabilities requires a systemic multi-level KT approach. Our Participation-KT roadmap, comprised of a framework and a list of principles and strategies for implementation, can be used to guide all stakeholders to foster a shift in practice. Forming partnerships and working collaboratively with all stakeholders is key for successful implementation.